Influence of Collaborative Strategic Reading Based on Social and Environmental Issues on Learning Reading Skills of Expository Texts - Widya Tristianti Prawira; Afnita; Amril Amir; Nofrahadi (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
Various research results conclude that reading skills of narrative texts such as expository texts are low in conventional learning that is closely tied to textbooks in high school. The main causal factor is believed to be the use of learning models that are closely tied to textbooks published by the state in annual units. The collaborative strategic reading model is believed to be interesting in learning reading skills. This study aims to describe: 1) the learning outcomes of expository text reading skills using conventional models in Indonesian textbooks in the control class; 2) the learning outcomes of expository text reading skills using the collaborative strategic reading model through special teaching materials in the treatment class; 3) the effect of the collaborative strategic reading model in learning expository text reading skills. This study was conducted in the odd semester of the 2026/2026 academic year at SMA Negeri 2 Batang Anai. This study used a quantitative approach with a posttest only control group experimental design. The study population was 67 grade X students of SMA Negeri 2 Batang Anai who were divided into two parallel classes. The research instrument was an objective test of expository text reading skills. The sample was determined as 65 students; 32 students in the control group and 33 students in the treatment group. The research data were analyzed using one-sample t-test and paired-sample t-test. The results of the study: 1) the learning outcomes of expository text reading skills in the control class were in the medium category; 2) the learning outcomes of expository text reading skills for the treatment group were in the high category; 3) the collaborative strategic reading model had a positive effect on expository text reading skills.